2015
DOI: 10.1038/srep08534
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CYP2C9 by MicroRNA hsa-miR-128-3p in Human Liver Cells and Association with Hepatocellular Carcinoma

Abstract: Published studies have identified genetic variants, somatic mutations, and changes in gene expression profiles that are associated with hepatocellular carcinoma (HCC), particularly involving genes that encode drug metabolizing enzymes (DMEs). CYP2C9, one of the most abundant and important DMEs, is involved in the metabolism of many carcinogens and drugs and is down-regulated in HCC. To investigate the molecular mechanisms that control CYP2C9 expression, we applied integrative approaches including in silico, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 41 publications
3
88
0
Order By: Relevance
“…miRNAs were selected for in silico analysis according to two criteria: (1) miRNAs that down-regulate the cognate genes in a opposite direction, and (2) the free energy of the miRNA:mRNA hybridization was ≤ −20 kcal/mol (based on our previous studies (Yu et al 2015a, c)). As shown in Table 1, 29 miRNAs were predicted to target 97 genes, and detailed prediction results are summarized in Supplementary Table 5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…miRNAs were selected for in silico analysis according to two criteria: (1) miRNAs that down-regulate the cognate genes in a opposite direction, and (2) the free energy of the miRNA:mRNA hybridization was ≤ −20 kcal/mol (based on our previous studies (Yu et al 2015a, c)). As shown in Table 1, 29 miRNAs were predicted to target 97 genes, and detailed prediction results are summarized in Supplementary Table 5.…”
Section: Resultsmentioning
confidence: 99%
“…The pGL3-CU vector that expresses Firefly luciferase and described in our previous reports (Yu et al 2015a, c) was used to create reporter gene plasmids. Firstly, the core 3′-UTRs of CYP3A4 , HNF1A , HNF4A and NR1I2 genes that contain the targeting elements for cognate miRNAs were produced by PCR amplification (all primers or oligonucleotides used in this study were purchased from Integrated DNA Technologies (Coraville, IA), and listed in Supplementary Table 7), and subcloned into the linearized nicked pGL3-CU vector to create CYP3A4-CU, HNF1A-CU, HNF4A-CU, and NR1I2-CU constructs, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From our previous study, we realized that the free energy associated with binding between miRNAs and mRNA targets is a critical parameter for predicting the interactional efficiency and stability of miRNA/mRNA complexes [23]. Here, in silico target prediction and free energy calculations indicated that hsa-miR-29a-3p could potentially target the coding region of CYP2C19 transcripts with a free energy of −23.3 kcal/mol.…”
Section: Discussionmentioning
confidence: 99%
“…There are also many other experimentally evaluated CYP gene regulation by miRNAs (Table 1), including CYP1A1 by miR-892a (Choi et al, 2012), CYP2C8 by miR-103 and miR-107 , CYP2C9 by miR-128-3p and miR-130b (Rieger et al, 2015;Yu et al, 2015a), CYP2E1 by miR-378 and miR-570 (Mohri et al, 2010;Nakano et al, 2015), CYP2J2 by let-7b (Chen et al, 2012a), and CYP24A1 by miR-125b . The effects of miR130b on endogenous CYP2C9 enzymatic activity (e.g., tolbutamide hydroxylation) in HepaRG cells were demonstrated by selective liquid chromatography-coupled tandem mass spectrometry assay (Rieger et al, 2015).…”
Section: Micrornas In Posttranscriptional Gene Regulationmentioning
confidence: 99%